Theologico-Moral Interpretation of Leviticus 18:21 and 20: 2-5 in the Context of Wealth-Induced Ritual Killings and its Implications for Socio-Economic Security in Nigeria - Festus Osom Omosor; Chibeze Igba Obigbor (Pinisi Journal of Social Science, 2026)
Ritual killing and human sacrifice are ancient practices preserved in various oral and literary traditions, including the Old Testament. While ancient Israel borrowed the practice from the traditions of the Ancient Near East, there is evidence that it was deprecated by Yahweh in the Old Testament, owing to the sanctity of life, and this is significant in present-day society. The increasing incidence of ritual killings motivated by the quest for wealth has become a major moral, religious, and security challenge, threatening human dignity, public safety, and national development. This study is a moral and theological interpretation of Leviticus 18:21 and 20:2-5 in the context of wealth-induced ritual killings and the implications for social security in Nigeria. The study is qualitative, descriptive and analytical in approach, employing historical-grammatical and contextual exegetical methods. The findings revealed that Leviticus 18:21 and 20:2-5 unequivocally condemn ritual killing and human sacrifice as violations of God's holiness and the sanctity of human life. It also found that wealth-induced ritual killings in Nigeria are fuelled by greed, materialism, unemployment, weak moral values, and the desire for quick wealth, and these practices have adversely affected human dignity and society in general. The study concludes that the theological and moral teachings of Leviticus 18:21 and 20:2–5 remain relevant in addressing wealth-induced ritual killings in Nigeria. It recommends strengthening moral and religious education, effective law enforcement, and promoting biblical values that uphold the sanctity of human life, justice, and accountability as essential measures to enhance social and economic security.